PENGARUH WAKTU PEMBERIAN MIKORIZA TERHADAP PERTUMBUHAN DAN HASIL TANAMAN MENTIMUN (CUCUMISSATIVUS L. )VARIETAS HARMONY - Bussa, Leni Oktaviana; Putra, Nyoman Labek Suyasdi; Hanum, Farida (Agrimeta: Jurnal Pertanian Berbasis Keseimbangan Ekosistem, 2019)
This study aims to determine the exact time of administration of mycorrhizae to the growth and yield of harmony varieties of cucumber plants. This study used a randomized block design (RBD) with 5 treatments when giving mycorrhizal and 5 replications. The treatment in question is without mycorrhiza (TM), administration of mycorrhizae 1 week before planting (M-1), administration of mycorrhiza at planting (MST), administration of mycorrhizae 1 week after planting (M + 1) and administration of mycorrhiza 2 weeks after planting (M +2). Parameters observed included plant height (cm), number of leaves per plant (strands), age at flowering (hst), number of fruit crops, weight of fruiting (g) and total fruit weight of crop (kg). Based on the results of statistical analysis showed that the M-1 treatment had the best effect with the maximum plant height (at the age of 3 mst) the highest 62.50 cm, the maximum number of leaves (at the age of 3 mst) the highest 18.30 strands, the age at the fastest flowering 14 , 90 days, the highest number of fruits per plant was 16.30, and the total fruit weight of the plant was 5.980 kg, while in the weight parameter, that was when compared with the treatment without mycorrhizal, the M + 1 treatment gave the highest yield per fruit, 0.514 g.